Karakteristik Gaya Komunikasi Presiden Jokowi Dalam Pengambilan Kebijakan - Drina Intyaswati; Mansur Mansur (ARISTO, 2017)
The mass media bring news about the various issues that arise in the community, including those related to communication styles of President Jokowi in communicating policies. The last case, in which ministers make "political noise" that attacked each other in front of the public, many people questioned about coordination between Jokowi and his officials. Furthermore, researchers set problems taken in the study,  1) How is the characteristic of Jokowi’s communication style in communicating policies 2) How is the communication competencies possessed by Jokowi?. Research using qualitative research methods with a macrostruktural discourse analysis approach. The population are  news about communications by President Jokowi, where the medium used is the online media. Online media selected in sampling are News.detik.com and Kompas.com which is the most popular news providers (version ALEXA per February 18, 2015). The results showed that the characteristic of Jokowi’s communication style in communicating policies in general is controlling style, although in some situations also use communication styles in accordance with existing conditions. Based on an analysis of the communication’s Jokowi in communicating policies, Jokowi’s communication competence covering aspects of commitment and confidence, empathy, flexibility, senstivity of  consequences, and proficiency.